Correlation of Stature and Head Circumference in Uttar Pradesh Population - Singh, Ekata; Shakya, Pratibha; Shakya, Neelesh Kumar (Academia Anatomica International, 2020)
Background: Anthropometry is the measurement of different parameters of any human individual. Anthropometry was first developed in 19th century. It was introduced by French police officer Alphonse Bertillion in 1883. Anthropometric measurements are important for identifying unknown bodies. The objectives is to the aim of present study is measuring head circumference and stature and their correlation so that a conclusion can be drawn about the correlation between these two parameters. Subjects and Methods: The study was conducted in the department of Anatomy, IIMS&R, Integral University, Lucknow. The present study group was done on 400 healthy individuals between 18-30 years of age (200 males & 200 females) of Uttar Pradesh population. Measurement of head circumference and stature was done and then stature was correlated with the head circumference. Written consent was taken before the assessment. This study was ethically approved by IIMS& R Institute research and ethical committee. Data was statistically analyzed. Results and Conclusions: In present study it was found that measurements of both the parameters (head circumference and stature) was higher in males in comparison to females. There was positive correlation between stature and head circumference.